2018
DOI: 10.1051/0004-6361/201731795
|View full text |Cite
|
Sign up to set email alerts
|

The GALEX Ultraviolet Virgo Cluster Survey (GUViCS)

Abstract: Context. At low redshift, early-type galaxies often exhibit a rising flux with decreasing wavelength in the 1000–2500 Å range, called “UV upturn”. The origin of this phenomenon is debated, and its evolution with redshift is poorly constrained. The observed GALEX FUV-NUV color can be used to probe the UV upturn approximately to redshift 0.5.Aim. We provide constraints on the existence of the UV upturn up to redshift ~0.4 in the brightest cluster galaxies (BCG) located behind the Virgo cluster, using data from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Ali et al (2018a) compared the UV upturn colours for galaxies in the Coma, Fornax and Perseus clusters, and found no evidence that the UV upturn was affected by the environment, a conclusion also reached by Smith et al (2012b) when comparing galaxies in the Coma and Virgo clusters. Similarly, the UV upturn colour of brightest cluster galaxies in the samples of Loubser & Sánchez-Blázquez (2011) and Boissier et al (2018) did not appear to depend strongly on cluster properties. However, it would be interesting to extend this to several cluster environments and consider the eventual dependence on position within the cluster and on kinematics.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Ali et al (2018a) compared the UV upturn colours for galaxies in the Coma, Fornax and Perseus clusters, and found no evidence that the UV upturn was affected by the environment, a conclusion also reached by Smith et al (2012b) when comparing galaxies in the Coma and Virgo clusters. Similarly, the UV upturn colour of brightest cluster galaxies in the samples of Loubser & Sánchez-Blázquez (2011) and Boissier et al (2018) did not appear to depend strongly on cluster properties. However, it would be interesting to extend this to several cluster environments and consider the eventual dependence on position within the cluster and on kinematics.…”
Section: Introductionmentioning
confidence: 80%
“…Differences in the originating mechanisms or timescales may be reflected in different evolutionary histories for galaxies in clusters and the field. Atlee et al (2009) finds a slow decrease in the strength of the upturn for a sample of bright field elliptical galaxies at 0 < z < 0.65 compared to the nearly constant colour for very bright ellipticals in the works of Brown et al (1998bBrown et al ( , 2000Brown et al ( , 2003 and brightest cluster galaxies (Loubser & Sánchez-Blázquez 2011;Boissier et al 2018). In our work on much larger samples of cluster early types with luminosities down to L * , we also see no evolution at z < 0.55 (Ali et al 2018a,b,c) but then detect a rapid reddening in the UV colour at z = 0.7; this may be consistent with the last data point in Atlee et al (2009), despite the large errors and small number statistics.…”
Section: Introductionmentioning
confidence: 92%
“…The observed COS G130M continuum is similar in shape to the IUE spectrum. The origin of the FUV excess is somewhat unclear, but FUV excesses are common in elliptical galaxies and seem to be tied to some late stage of stellar evolution (see reviews by O'Connell 1999 and Brown 1999 and more recent work by Yi et al 2011 andBoissier et al 2018). Fitting a low-order polynomial to the observed FUV continuum, we estimate the observed FUV continuum luminosity (from 1160Å to 1450Å) in this aperture to be 2.4 × 10 38 erg s −1 .…”
Section: Fuv Continuummentioning
confidence: 99%
“…Also, Ree et al (2007) examined the (FUV-V) colour of nearby elliptical galaxies and those in clusters up to z = 0.2, as well as other two clusters at z = 0.3 and z = 0.5; this study indicated a feeble evolution of this colour. Recently Ali et al published a series of papers revisiting the UV upturn discussion (Ali et al 2018a,b,c;Ali et al 2019) as well as Boissier et al (2018). To explore the evolution of the UV upturn, Ali et al (2018c) selected data from four galaxy clusters (one at z ≈ 0.31, two at z ≈ 0.55, and one at z ≈ 0.68), retrieved from the Hubble Space Telescope (HST) Legacy Archive 1 ; they concluded that the incidence of the phenomenon rises up until z ≈ 0.55 and then it strongly declines, suggesting that, in fact, the UV upturn depends on redshift.…”
Section: Introductionmentioning
confidence: 99%